Fatigue Strength and Life Prediction of a MAR-M247 Nickel-Base Superalloy Gas Turbine Blade with Multiple Carbide Inclusions - Lin, H.; Geng, H.P.; Zhang, Y.Y.; Li, H.; Liu, X.Y.; Zhou, X.F.; Yu, L. (Проблемы прочности, 2019)
Casting of a gas turbine blade from MAR-M247 nickel-base superalloy is followed by multiple carbide precipitates as a result of solidification. The microstructure of carbide was established with scanning electron microscopy and energy spectrum analysis. A finite element model simulating the blade with a random carbide precipitate is constructed using ANSYS software, and stress-strain evaluation is performed. The blade operation conditions are realized in a vibratory-tensile combined test setup with stress measurements using strain gauges arranged on different parts of the blade. The respective von Mises equivalent stresses obtained in simulation and test measurements are found to be comparable and can be used to assess the blade fatigue life based on the available fatigue curves and Palmgren–Miner rule of damage accumulation. Simulation and experimental results are the basis for plotting the relationship between the volumetric ratio of precipitates in the blade and its fatigue life. The results obtained at room temperature can; be extrapolated to the elevated ones to provide more reliable prediction of the superalloy blade fatigue and creep-fatigue life values. Литье лопатки газовой турбины из суперсплава на никелевой основе MAR-M247 сопровождается образованием множественных карбидных выделений в результате затвердевания. Микроструктуру карбида изучали с помощью сканирующей электронной микроскопии и энергетического спектрального анализа. Построена конечноэлементная модель лопатки со случайным карбидным выделением на основе программного обеспечения ANSYS, выполнена оценка напряженно-деформированного состояния. Условия эксплуатации лопатки реализовали на экспериментальной установке для комплексного испытания на вибрацию и растяжение, напряжения измеряли с помощью тензодатчиков, размещаемых на различных участках лопатки. Проведено сравнение эквивалентных напряжений по Мизесу, полученных при моделировании и экспериментально. Установлено, что их можно использовать для оценки усталостной долговечности лопатки на основании полученных кривых усталости и закона накопления повреждений Палмгрена Майлера. Они служат также основой построения зависимости между объемным соотношением включений в лопатке и ее усталостной долговечностью. Данные, полученные при комнатной температуре, могут быть экстраполированы на повышенные, что обеспечивает более достоверный прогноз усталости и усталостной долговечности лопатки из суперсплава при ползучести. Лиття лопатки газової турбіни з суперсплавів на нікелевої основі MAR-M247 супроводжується утворенням множинних карбідних виділень в результаті затвердіння. Мікроструктуру карбіду вивчали за допомогою скануючої електронної мікроскопії та енергетичного спектрального аналізу. Побудована скінченноелементна модель лопатки з випадковим карбідним виділенням на основі програмного забезпечення ANSYS, виконана оцінка напружено-деформованого стану. Умови експлуатації лопатки реалізували на експериментальній установці для комплексного випробування на вібрацію і розтягнення, напруги вимірювали за допомогою тензодатчиків, що розміщуються на різних ділянках лопатки. Проведено порівняння еквівалентних напружень по Мізесу, отриманих при моделюванні і експериментально. Встановлено, що їх можна використовувати для оцінки втомної довговічності лопатки на підставі отриманих кривих втоми і закону накопичення ушкоджень Палмгрена-Майлера. Вони служать також основою побудови залежності між об'ємним співвідношенням включень в лопатці і її втомної довговічністю. Дані, отримані при кімнатній температурі, можуть бути екстрапольовані на підвищені, що забезпечує більш достовірний прогноз втоми і втомної довговічності лопатки з суперсплавів при повзучості.